2015
DOI: 10.1007/s10554-015-0696-9
|View full text |Cite
|
Sign up to set email alerts
|

One-point carotid wave intensity predicts cardiac mortality in patients with congestive heart failure and reduced ejection fraction

Abstract: Wave intensity (WI) is a hemodynamic index used to evaluate the interaction between the heart and the arterial system, measured with an echo-Doppler system at the level of the common carotid artery. WI has two peaks: W1 during early systole that represents left ventricular (LV) contractility, and W2 in late systole that is related to the inertia force during isovolumetric relaxation. The aim of this study was to determine whether WI parameters improve the prediction of poor outcome in patients with heart failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The increase in arterial diameter with increasing age causes a decrease in both viscoelasticity and strain-stiffening as modelled by equations (5), (6) and (10). Hence, the older the subject, the smaller the differences Figure 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in arterial diameter with increasing age causes a decrease in both viscoelasticity and strain-stiffening as modelled by equations (5), (6) and (10). Hence, the older the subject, the smaller the differences Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these variations, the stiffness parameter b and the viscoelastic parameter G calculated through equations (6) and 7were changed through a combination of the formula for estimating wall thickness and the multipliers for diameter, PWV and wall viscosity.…”
Section: Baseline Model and The Generation Of Virtual Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] For all these reasons, efforts are increasingly being targeted toward early diagnosis for intervening at an earlier stage of disease. Italian Society of Echocardiography has been involved from its origins in preventive field, developing several research programs,[4567891011121314] including Disfunzione Asintomatica VEntricolare Sinistra[15] study (on cardiac field), and considering deeply prognostic implications of vascular disease.…”
Section: The Role Of the Italian Society Of Cardiovascular Echographymentioning
confidence: 99%
“…Arterial pulse waves carry information about the performance of the heart and vessels, and several studies have identified statistically significant changes in the metrics derived from wave intensity (WI) in the presence of impaired heart performance (Curtis et al, 2007;Siniawski et al, 2009;Li and Guo, 2013;Takaya et al, 2013;Vriz et al, 2015) but only when averaged over groups. Furthermore, WI has generally been determined from measurements of blood velocity and pressure made throughout the cardiac cycle (Parker, 2009), but pressure waveforms with sufficient temporal resolution can only be obtained accurately by invasive methods or estimated inaccurately by noninvasive ones, which has inhibited the clinical realisability of WI-based diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%